SYNTHESIS OF VALUABLE FUEL ADDITIVE SOLKETAL FROM BIO-GLYCEROL OVER ACID ACTIVATED META KAOLIN CLAY CATALYST - ZAHID, IMTISAL (2021)
World facing the energy shortage which raised some environmental concerns like greenhouse effect and global warming situation. Biodiesel, which is made from animal fats and vegetable oils, has grown in popularity as a more environmentally friendly alternative to fossil fuels. Increased demand and production of biodiesel results in surplus of glycerol production that leads to a drastic decline in the glycerol price. As the vast amount of produced crude glycerol cannot be dumped and used directly which raises environmental concerns. Bulk of bio glycerol required successful techniques to transform into valuable green product to improve the sustainability of the biodiesel production chain. On the other hand, alternative and valuable successful techniques must be introduced for the utilization of bio glycerol into valuable chemical or fuel additive. One of the promising processes is glycerol conversion into fuel additive a solketal which is useful additive in biodiesel or gasoline to enhance the octane number and to control the emissions. This study introduces an ecofriendly and valueless process of solketal synthesis from glycerol. The novelty of this work is utilization of meta kaolin as a catalyst for acetalization process. Moreover, kaolin clay catalysts are low cost, abundantly available, eco-friendly and one of the promising applications for the solketal synthesis. The catalytic properties of raw kaolin clay were improved by easy acid activation technique and modification in physicochemical or textural properties were determined by using X-rays Diffraction (XRD), Fourier Transform Infra-Red (FTIR) spectroscopy, Brunauer–Emmett–Teller (BET), and Field Emission Scanning Electron Microscope. Acid activated meta kaolin K3 exhibited significant catalytic and surface properties. Acetalization of glycerol with acetone to produce solketal over meta kaolin catalysts introduces a unique, ecofriendly, and inexpensive process.